Association of Organochlorine Pesticides With Genetic Markers of Endoplasmic Reticulum Stress in Type 2 Diabetes Mellitus: A Case–Control Study Among the North-Indian Population - Tawar, Neha; Banerjee, Basu Dev; Madhu, Sri Venkata; Agrawal, Vivek; Gupta, Sanjay (Frontiers in endocrinology (Lausanne), 2022)
Organochlorine pesticides (OCPs) have been long linked to type 2 diabetes mellitus (T2DM); however, this relation at the molecular level has not been explored yet. Endoplasmic reticulum (ER) stress and pro-inflammatory pathways are considered vital ones in the pathogenesis of T2DM. We aimed to investigate the existence of any association between OCPs, ER stress, and pro-inflammatory pathways in subjects with known T2DM. Seventy subjects each with T2DM and normal glucose tolerance were recruited from the surgery department. Their visceral adipose tissue was collected intraoperatively. OCP concentration, ER stress, and pro-inflammatory markers were analyzed and compared between two study groups. We found 18 OCPs and their metabolites in visceral adipose tissue samples of study participants. The levels of δ-HCH, heptachlor, endrin, and p,p'DDT were significantly higher in the T2DM group and were also positively correlated with fasting and postprandial plasma glucose levels (p < 0.01). We observed a positive association of δ-HCH (p < 0.01), heptachlor (p < 0.05), and endrin (p < 0.05) with central adiposity and ER stress markers. However, we failed to establish the correlation of OCPs with any of the pro-inflammatory markers. The existence and simultaneous complex correlation of OCPs with ER stress may explain their role in the pathogenesis of T2DM, revealing the persistence of the gene-environment interaction in the etiology of T2DM.